Nilai Keagamaan dan Moderasi Beragama : Upaya Pencegahan Permasalahan di Media Sosial - Sastrawardana, Viqia (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
With this research, a researcher can study and analyze cases that occur on social media, representation of religious values and moderation of various efforts to prevent problems on social media. This research uses library research analysis methods and digital observation to deepen an analysis of cases that occur on social media related to religion and religious moderation. The large contribution of religious moderation is not far from problems on social media with issues off discrimination, SARA, minorities and the majority of cultural, religious, ethnic and racial diversity in virtual spaces on social media. Instilling and strengthening religious moderation and core religious values to prevent problems on social media through religious education, a frame of tolerance, harmonization and radical action.